Cutaneous mucosal immune-parameters and intestinal immune-relevant genes expression in streptococcal-infected rainbow trout (Oncorhynchus mykiss): A comparative study with the administration of florfenicol and olive leaf extract. Issue 107 (December 2020) - Shiry, Nima; Khoshnoodifar, Khadije; Alavinia, Seyed Jalil
Abstract: This study evaluated changes in cutaneous mucosal immunity (total protein (TP) and immunoglobulin (TIg), lysozyme, protease, esterase, and alkaline phosphatase (ALP)) and some immune-related genes expression (tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-8, hepcidin-like antimicrobial peptides (HAMP), and immunoglobulin M (IgM)) in the intestine of rainbow trout ( Oncorhynchus mykiss ) orally-administrated florfenicol (FFC) and/or olive leaf extract (OLE), experimentally infected with Streptococcus iniae . The juvenile fish (55 ± 7.6 g) were divided into different groups according to the use of added OLE (80 g kg −1 food), the presence/absence of FFC (15 mg kg −1 body weight for 10 consecutive days), and the streptococcal infectivity (2.87 × 10 7  CFU mL −1 as 30% of LD50 -96h). The extract's chemical composition was analyzed using the high-performance liquid chromatography (HPLC) system. The skin mucus and intestine of fish were sampled after a 10-day therapeutic period for all groups, and their noted indices were measured. Our results signified that the oleuropein, quercetin, and trans -ferulic acid were the most obvious active components of OLE which were found by HPLC analysis. The combined use of OLE and FFC could lowered some skin mucus immunological indices (e.g., TP, TIg, and ALP), and the gene expression of inflammatory cytokines (e.g., TNF- α and IL-1 β) of rainbow trout. Moreover, lysozyme and protease activities respectively were invigorated by the FFC and OLE treatment. Also, the use of OLE as a potential medicine induced the gene expression of HAMP. As the prevention approach, it would be recommended to find the best dose of OLE alone or in combination with the drug through therapeutics period before the farm involved in the streptococcal infection. Highlights: The most obvious active component of olive leaf (OLE) extract has been oleuropein (0.496 mg L −1 ). The combined use of OLE and FFC could relieved the gene expression of inflammatory cytokines. The lysozyme and protease activities respectively were invigorated by the FFC and OLE treatment. The use of OLE as a potential medicine induced the gene expression of hepcidin-like antimicrobial peptides.